MEMBANGUN KESADARAN DIGITAL: PENDAMPINGAN DAN SOSIALISASI HUKUM DAN UNDANG-UNDANG ITE DI MA AL-FALAH TLANAKAN PAMEKASAN - Asyhari Asyhari; Jalaludin Faruk Azhari (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The development of the digital era has had a huge influence on the lives of the younger generation, especially marked by the increasing intensity of social media use. This research aims to strengthen students' legal awareness of the Electronic Information and Transaction Law (ITE Law) as a preventive effort in suppressing the potential for digital crime among MA Al-Falah Tlanakan students. The method of implementing activities includes the preparation stage, the implementation of socialization, and evaluation. This activity was held on October 12, 2025, involving 20 students from grades X, XI, and XII. The results of the study showed a significant increase in the average score of students. These findings show that the socialization program implemented is effective in increasing students' digital literacy and legal awareness, so that they are able to use technology more wisely, responsibly, and avoid behavior that has the potential to cause violations of the law in the digital realm.